2012
DOI: 10.5796/electrochemistry.80.327
|View full text |Cite
|
Sign up to set email alerts
|

<i>Acidithiobacillus ferrooxidans</i> as a Bioelectrocatalyst for Conversion of Atmospheric CO<sub>2</sub> into Extracellular Pyruvic Acid

Abstract: This study investigated the ability of the bacterium Acidithiobacillus ferrooxidans to convert CO 2 into organic compounds in batch culture and during electrochemical cultivation. Metabolites secreted into the culture medium were detected and analyzed by HPLC and mass spectroscopy, which revealed that pyruvic acid was one of the organic acids present in both cultures. We found that although pyruvic acid acted as a strong inhibitor for microbial growth in batch cultures, microbial CO 2 fixation activity in elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 10 publications
(8 reference statements)
1
7
0
Order By: Relevance
“…In the presence of Fe 2+ ions, the onset potential for cathodic current generation was estimated to be +0.65 V, as indicated in the peak in the logarithmic plot for current. This value is close to the redox potential of Fe 3+ /Fe 2+ couple and consistent well with the previously reported model for electrochemical cultivation of A. ferrooxidans ( Yunker and Radovich, 1986 ; Matsumoto et al, 1999 , 2002 ; Ishii et al, 2012 ). Namely, diffusible Fe 2+ and Fe 3+ ions serve as an electron shuttle which bridges electron transfer between planktonic cells and electrodes.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…In the presence of Fe 2+ ions, the onset potential for cathodic current generation was estimated to be +0.65 V, as indicated in the peak in the logarithmic plot for current. This value is close to the redox potential of Fe 3+ /Fe 2+ couple and consistent well with the previously reported model for electrochemical cultivation of A. ferrooxidans ( Yunker and Radovich, 1986 ; Matsumoto et al, 1999 , 2002 ; Ishii et al, 2012 ). Namely, diffusible Fe 2+ and Fe 3+ ions serve as an electron shuttle which bridges electron transfer between planktonic cells and electrodes.…”
Section: Resultssupporting
confidence: 92%
“…To evaluate the redox potential of electrical conduits established at the cell-electrode interface, electrodes covered with viable cells were examined by linear sweep (LS) voltammetry (solid line, Figure 2 ). As a reference, we also conducted LS voltammetry for cell cultures containing soluble Fe 2+ ions, a system known as electrochemical cultivation of A. ferrooxidans (broken line, Figure 2 ) ( Yunker and Radovich, 1986 ; Matsumoto et al, 1999 , 2002 ; Ishii et al, 2012 ). In the presence of Fe 2+ ions, the onset potential for cathodic current generation was estimated to be +0.65 V, as indicated in the peak in the logarithmic plot for current.…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that Thiobacillus could oxidize S(0) to release electrons and gain energy to synthesize metabolites to reduce Cr(VI). 56,57 The accumulated Blvii28 (17.9%) might play an important role in autotrophic S(0) oxidation in B−S, which has been reported to be able to generate hydrogen for S(0) autotrophic microbes. 58 In both B−S and B−Fe, archaeal communities were also observed to shift significantly.…”
Section: Environmental Science and Technologymentioning
confidence: 99%
“…Its metabolic capability has led to its utilization in bioprocesses including copper bioleaching and desulfurization of coal and sour gases (Monticello and Finnerty, 1985). We have been investigating these cells for use as a unique biotechnology platform enabling biofuels and biomass to be produced from carbon dioxide and electricity (termed electrofuels) (Conrado et al, 2013;Ishii et al, 2012;Li and Liao, 2013;Nybo et al, 2015). We have reported the genetic modification of A. ferrooxidans to produce exogenous chemicals (isobutyric acid [IBA] or heptadecane) from carbon dioxide (Kernan et al, 2015).…”
Section: Introductionmentioning
confidence: 99%